Aging, mating, and the evolution of mtDNA heteroplasmy in Drosophila melanogaster - Kann, Lisa M. (The National Academy of Sciences, 1998)
Heteroplasmy, the presence of more than one type of mtDNA within cells, is common in animals and has been associated with aging and disease in humans. Changes in the frequencies of mtDNA variants between cell and animal generations thus bears on the evolution of mtDNA and the progression of diverse pathologies. We have used densitometry of Southern blots of individual heteroplasmic Drosophila melanogaster to study the effects of age, increased egg production after mating, and temperature on evolution of heteroplasmy within and between generations. The frequency of the longer mtDNA variant consistently increased between early and late cohorts of F(1) offspring derived from 18 independent heteroplasmic mothers as they aged. Neither temperature (flies maintained at 25°C and 18°C) nor the holding of flies as virgins for 10 days before mating had significant effects on transmission patterns. However, at the ends of their lives, flies that had laid eggs at 25°C had a greater frequency of the long mtDNA than did their siblings who had laid eggs at 18°C. The evolution of heteroplasmy within a generation was studied in samples of siblings that either were mated or held as virgins, and then scored for mtDNA haplotype frequencies at two different ages (day 2 and day 14). Mated flies showed a significantly greater increase in the frequency of the long mtDNA variant with age than did the unmated flies. This system provides a model for the joint analysis of generational and chronological age in the transmission dynamics of a molecular polymorphism.